Vocational Interest Regarding Career Awareness among Adolescent Boys and Girls of Rohtak City; Haryana (India) - Sharma, Karuna (International Research Journal of Management, IT & Social Sciences (IRJMIS), 2016)
All young are deeply concerned about their future vocational roles. Vocation is valued by most adolescents, for its contributions to self-esteem, financial independence, and social maturity. The present study is done to find out the gender difference in vocational interest of high school adolescents. The sample for the investigation consisted of 300 adolescents (150 boys & 150 girls) studying in 10th class. The sample was taken from six schools of Rohtak city. Standardized tool was used to measure the variable Vocational Interest Record (VIR) (Kulshrestha, 1984). For analysis of data, mean, standard deviation, and t-test were computed. The results of the study revealed that, gender difference in vocational interest was seen. Results indicated that t scores on artistic, agricultural, social and house hold dimensions of vocational interest were significant. Significant different exists between boys and girls on above vocational areas. Girls were high on artistic, social and house hold jobs as compared to boys whereas boys were high on agricultural jobs.Â